(untitled) (Global Journal of Science Frontier Research, 2017)
When Hurricane Isaac in 2012 was over the coastal regions of Louisiana, USA, simultaneous measurements of both positive and negative storm surges were made by the U. S. National Ocean Service. Analysis of these datasets including wind speed and direction indicates that 93% of the positive surge and 74% of the negative surge can be explained by the windstress forcing, respectively. It is also found that the ratio of wind stress to either positive or negative surge is approximately 1:1.5, meaning that one pascal (1 N m -2 ) wind stress can generate 1.5 meters of water-level increase or decrease. This ratio may be used for forecasting or hind-casting purpose.